Texture evolution in building direction of wire arc additive manufactured 316L stainless steel with high plasticity - Hang Dong; Yongcun Li; João Pedro Oliveira; Sheng Gao; Wenjun Zhu; Yong Wang (Materials & Design)
Crystallographic orientation in polycrystalline materials impacts multiple properties including fatigue resistance, stress corrosion cracking resistance, and elongation. Currently arc-based directed energy deposition, also known as wire arc additive manufacturing (WAAM), is used for 316L stainless steel (SS), offering high strength and ductility. However, process-induced defects, process parameters, and heat history can affect the quality of the material. In this study, the selection of gas metal arc welding as the heat source, followed by air cooling, was made for the fabrication of 316L SS components on a low-carbon steel substrate, aiming to optimize the manufacturing process. Ex-situ and in-situ tensile tests were performed. The microstructure of the WAAMed 316L SS is composed of nano α’, nano MnSiO3, and columnar γ with a dominant growth direction of {001}. When tested along the building direction (BD) the material possessed excellent elongation up to 95 % strain, while in the radial direction (RD) an increase in yield strength was observed. The BD sample exhibits reorientation with increased strain, with dominant textures being {113} < 631>, {114} < 841>, {123} < 013>, and {123} < 391 > . The deformation process is governed by dislocation slip, with multiple slip systems activated.